Effect of Solution Annealing Treatments on Formabilityof Stainless Steel Alloys - Ali Alrabii, Samir; B. Rahmetallah, H.; A. Abdulallah, M. (Journal of Engineering and Sustainable Development, 2011)
The effect of solution annealing treatment on the formability of three stainless steel alloys (AISI 321, GOST A917, and SAF 2205) has been studied. Properties obtained from tensile testing (strength, ductility, strain hardening index, and strain rate sensitivity) have been chosen as criteria to detect formability. The values of those criteria were compared with stretching behavior obtained from Olsen test (h-value). Solution annealing treatment, at the range 900-1350oC for 30 min. followed by water quenching, which showed a remarkable effect on formability for the three alloys. Annealing the duplex stainless steels at 950oC and at temperatures higher than 1050oC, was found to decrease the strain hardening index (formability) due to the formation of brittle phases during annealing at 950oC, and also due to increase of ferrite content when annealing at temperatures higher than 1050oC. The rate of cooling (water quenching, air cooling, and furnace cooling) after annealing at 1050oC showed to have an effect on the formability of the three alloys in a way that air cooling and water quenching produced better formability than furnace cooling due to formation of brittle carbides and grain growth during furnace cooling.